SKRINING PENDENGARAN DENGAN PEMERIKSAAN AUDIOMETRI DAN KUESIONER HHIE-S SERTA PENYULUHAN GANGGUAN PENDENGARAN PADA LANSIA - Sudrajad, H.; Setiamika, M.; Hendradewi, S.; Primadevi, N.; Pratiwi, D.; Matea, A.; Gayatri, A.; Manurung, R. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p12, 2024)
Introduction : Presbycusis one of the issues that frequently affects the longer-term elderly population. This disorder is one of the aging processes that cannot be avoided because of the degenerative process of sensory cells in the inner ear and is difficult to correct. This disorder is often followed by social disorder which causes a decrease in the quality of life of the elderly. Purpose : To describe the hearing thresholds and psychosocial handicaps due to hearing. Methods : Descriptive study which was conducted at the Panti Wreda Widhi Asih and the ENT polyclinic at RSUD dr. Moewardi, Surakarta, Indonesia in March-May 2023. Subjects underwent audiometric examination and were interviewed according to the Hearing Handicap Inventory For The Elderly-Screening (HHIE-S) questionnaire. Results : This study consisted of 27 samples with details of 10 men and 17 women with an average age of 68.15 ± 10.30. The threshold mean with all subjects was 39.26 ± 15.78 dB while the mean HHIE-S score was 12.67 ± 10.87.   Conclusion: Most subjects have moderate hearing loss and have a mild-moderate impact on quality of life due to hearing loss. Education for the elderly and elderly caregivers is expected to improve the quality of life of the elderly.